PENGEMBANGAN MODUL LEARNING CYCLE 5E BERORIENTASI GREEN CHEMISTRY PADA MATERI SISTEM KOLOID UNTUK PENINGKATKAN LITERASI SAINS SISWA - Kimianti, Febyarni; Suryati, Suryati; Dewi, Citra Ayu (Hydrogen: Jurnal Kependidikan Kimia, 2016)
One of critical problems faced by students in learning process is lack of teaching materials. Teaching materials are selected by the teacher, and mostly they focuson a review of materials and problem solving, without considering environment aspect in learning. Therefore, the attitude of student toward environment and awareness of science are lacking. Ideally, students must be equipped with modules that can stimulate them to learn and have environment awareness. The purpose of this study was to determine the feasibility and effectiveness of a developed module. The module was developed by adopting ADDIE model, consisting of 1) analyze, 2) design, 3) develop, 4) implementation, and 5) evaluation. The study was conducted on class XII IPA3 at SMAN 1 Batukliang. At development stage, the validation results showed that the module is very feasible for use, as suggested by expert evaluation score of 96.04%, practitioner evaluation of 97.77%, as well as average score from students of 97.27%. Result of N-gain test shows that the average N-gain 0.8 demonstrating the remarkable effectiveness of module in improving the scientific literacy of students. Overall, it can be concluded that the developed module was highly feasible for use and can help to improve scientific literacy of students.